A new version of the ERICA tool to facilitate impact assessments of radioactivity on wild plants and animals. (March 2016) - Brown, J.E.; Alfonso, B.; Avila, R.; Beresford, N.A.; Copplestone, D.; Hosseini, A.
Abstract: A new version of the ERICA Tool (version 1.2) was released in November 2014; this constitutes the first major update of the Tool since release in 2007. The key features of the update are presented in this article. Of particular note are new transfer databases extracted from an international compilation of concentration ratios (CRwo-media ) and the modification of 'extrapolation' approaches used to select transfer data in cases where information is not available. Bayesian updating approaches have been used in some cases to draw on relevant information that would otherwise have been excluded in the process of deriving CRwo-media statistics. All of these efforts have in turn led to the requirement to update Environmental Media Concentration Limits (EMCLs) used in Tier 1 assessments. Some of the significant changes with regard to EMCLs are highlighted. Highlights: The ERICA Tool for performing environmental risk assessment has been updated. The new version is underpinned by an internationally supported transfer database. The Tool provides coverage for many organism groups and radioisotopes. New calculations were required to derive environmental media concentration limits. Modified approaches to deriving missing transfer parameters are elaborated.